Characterization of uranium mined ore for nuclear forensic applications - Ntsohi, Liteboho (My University, 2019)
Nuclear forensic science aims to ﬁnd signature of nuclear or radioactive material that can aid with the attribution process. Uranium compounds have isotopic or chemical characteristics that provide speciﬁc information concerning their origin and production process. Examples of such signatures are uranium and thorium isotopic and activity concentration, trace element content, rare earth elements, among others. This dissertation investigated the applicability of these signatures in environmental samples from uranium mining areas in Nigeria and Botswana using Inductively Coupled Plasma Mass Spectrometer (ICP-MS) and X-Ray Fluorescence (XRF), techniques. In this study uranium ore samples from ﬁve mining regions in Nigeria (Riruwai, Mika 1, Mika 2, Michika) and in Botswana (Serule) were analyzed to determine the isotopic and elemental signatures for the regions. The Uranium and Thorium isotopic and activity concentrations for these areas were compared to determined the signiﬁcance of the signatures in these regions. From the obtained data, both rare earth elements and impurity elements were determined and subjected to ANOVA in order to quantify their statistical signiﬁcance in the observed variations. For Nigeria samples, the results conﬁrm that REE and impurity element patterns used for origin location exhibit signiﬁcant variation within the considered mine areas. However, this variation can not be deduced from the Botswana samples despite further mineralogy analysis with XRF
A dissertation submitted to the Faculty of Science, University of the Witwatersrand, Johannesburg, in fulﬁllment of the requirements for the degree of Master of Science. 2019